2016
DOI: 10.1371/journal.pone.0161552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mild Thyrotoxicosis on Performance and Brain Activations in a Working Memory Task

Abstract: AimsDisturbed levels of thyroid hormones are associated with neuropsychiatric disorders, including memory impairments. The aim of this study was to evaluate effects of mild induced thyrotoxicosis on working memory and its neural correlates.MethodsTwenty-nine healthy, male subjects with normal thyroid state participated in the study. Functional MRI was acquired during a working memory task (n-back task) before and after ingesting 250 μg L-thyroxin per day for a period of eight weeks. In addition, neuropsycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 74 publications
2
16
0
Order By: Relevance
“…Our finding indicates reduced intra network FC in fronto‐parietal network regions, including frontal pole, middle frontal gyrus, inferior frontal gyrus, parietal operculum cortex, superior parietal lobule, supramarginal gyrus, in thyrotoxicosis patients compared to controls. The findings are in line with a previous task based functional study that showed impaired performance during the N‐back working memory task and altered BOLD activity in the prefrontal area, insula and parahippocampal regions in mild thyrotoxicosis . An earlier neuropsychological study also showed impairment in working memory, executive functions and attention in thyrotoxicosis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding indicates reduced intra network FC in fronto‐parietal network regions, including frontal pole, middle frontal gyrus, inferior frontal gyrus, parietal operculum cortex, superior parietal lobule, supramarginal gyrus, in thyrotoxicosis patients compared to controls. The findings are in line with a previous task based functional study that showed impaired performance during the N‐back working memory task and altered BOLD activity in the prefrontal area, insula and parahippocampal regions in mild thyrotoxicosis . An earlier neuropsychological study also showed impairment in working memory, executive functions and attention in thyrotoxicosis.…”
Section: Discussionsupporting
confidence: 92%
“…In thyrotoxicosis, thyroid gland produces excessive amounts of fT3 and fT4, leading to a suppression of serum TSH. Patients with thyrotoxicosis suffer from various neurocognitive issues, such as prominent nervousness, depression, anxiety, irritability, poor concentration, memory impairment and a decline in executive functions . Until now, the underlying mechanisms of these neurocognitive alterations in thyrotoxicosis patients has remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both neuroimaging studies and clinical evidence suggest a role of the cerebellum in cognitive processes . In previous studies, we were able to show that thyroid hormones have an effect on structure and function of the cerebellum . Animal studies show that the cerebellum is involved in the production of thyroid hormones and expression of thyroid hormone receptors .…”
mentioning
confidence: 81%
“…Numerous behavioural alterations have been described in patients with hypo‐ and hyperthyroidism . Only recently were these changes demonstrated to be supported by structural and functional brain changes . Particularly, the impact of thyroid hormone on memory functions has been shown not only using classical memory testing tasks , but also when testing for morphological changes .…”
mentioning
confidence: 99%